Away all boats! [videorecording (DVD)] - Pevney, Joseph; Chandler, Jeff, 1918-1961; Nader, George, 1921-2002; Dodson, Kenneth, 1907-1999; Eastwood, Clint, 1930- (Good Times Home Video Corp, 1999)
Capt. Jebediah Hawks must weld a new ship and her inexperienced crew into a well-oiled war machine. Highlighed by spectacular battles with kamikaze planes, this is the exciting story of the amphibious attack transports that landed U.S. troops in the laps of their Japanese enemies during World War II.